Global temporal and spatial changes of vegetation in desert steppe Ecosystems: Impacts of climate driving factors - Xiaonan Chen; Bochao Cui; Dongwei Gui; Qi Liu; Yunfei Liu; Qian Jin (Ecological Indicators)
Desert steppe ecosystems are crucial for global ecological stability and human well-being. This study provides a comprehensive analysis of long-term vegetation changes in desert steppes and their relationship with climatic factors, using GIMMS NDVI data (1993–2022) and multi-source climate datasets. The research finds that 82 % of global desert steppes are concentrated in Eurasia. Over the past 30 years, approximately 50 % of these ecosystems have experienced significant vegetation declines, with Central Asia being the most affected region, highlighting increased ecological vulnerability. Quantitative analysis shows that minimum temperature and vapor pressure contribute 7.26 % and 7.67 % to positive vegetation changes, respectively, while the leaf area index of low vegetation contributes the most (14.45 %), reflecting ecosystem resilience under favorable conditions. Conversely, solar radiation and surface pressure account for 29.38 % and 10.01 % of negative changes, respectively, with solar radiation having the most significant impact, particularly near critical aridity thresholds where ecosystem degradation is most pronounced. These findings underscore the urgency of targeted conservation efforts, particularly in Central Asia and the United States, to mitigate further degradation of desert steppes.